2023
DOI: 10.58838/2075-1230-2023-101-1s-51-56
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of photodynamic therapy in an experimental mice tuberculosis model

S. N. Belogorodtsev,
A. P. Lykov,
S. D. Nikonov
et al.

Abstract: The objective: to study the efficacy of antimicrobial photodynamic therapy (APDT) using hydroxyaluminum phthalocyanine (Photosens) as a photosensitizer in the experimental model of tuberculosis infection in mice.Subjects and Methods. Balb/cmice were infected with the multiple drug resistant (MDR) strain of M. tuberculosis Beijing BO/W148. APDT with hydroxyaluminum phthalocyanine and red laser light exposure were started on Day 45. A total of 4 sessions of APDT on the projection of both lungs, liver and spleen … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 14 publications
0
1
0
Order By: Relevance
“…When conducting aPDT using hydroxyaluminum phthalocyanine (Photosens) as a PS in an experimental model of tuberculosis infection in mice, it was demonstrated that the tissues of the experimental animal retain a significant amount of light energy. Nevertheless, the residual light transmission was sufficient to provide a pronounced therapeutic effect, manifested in a significant reduction of the mycobacterial load and specific inflammatory process in all examined internal organs [11]. However, side effects on the host organism were observed when using light with a high dose density (above 100 J/cm 2 ).…”
Section: Introductionmentioning
confidence: 95%
“…When conducting aPDT using hydroxyaluminum phthalocyanine (Photosens) as a PS in an experimental model of tuberculosis infection in mice, it was demonstrated that the tissues of the experimental animal retain a significant amount of light energy. Nevertheless, the residual light transmission was sufficient to provide a pronounced therapeutic effect, manifested in a significant reduction of the mycobacterial load and specific inflammatory process in all examined internal organs [11]. However, side effects on the host organism were observed when using light with a high dose density (above 100 J/cm 2 ).…”
Section: Introductionmentioning
confidence: 95%